2005
DOI: 10.1196/annals.1327.088
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Polychlorinated Biphenyls (PCBs) by Disturbance of Thyroid Hormone‐Regulated Genes

Abstract: PCBs are known as neurotoxic compounds. Part of this neurotoxicity could be due to an alteration of the expression of TH-regulated genes in brain. To identify such genes, brain protein extracts of hypo- and hyperthyroid as well as PCB-treated embryos were compared by fluorescent 2D-DIGE. In total, we observed 109 differentially expressed proteins, of which 17 differed with both PCB and hypo- or hyperthyroid treatment. It was found that the interaction of PCBs with the expression of TH-regulated genes is congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…A broad spectrum of neurotoxicants (e.g., environmental pollutants such as metals, pesticides, and PCBs) has been shown to cause LM deficits after sub-chronic exposure (Roelens et al, 2005;Lidsky and Schneider, 2003;Ishimine et al, 2003). However, from the behavioral effects, it is difficult to deduce information about underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A broad spectrum of neurotoxicants (e.g., environmental pollutants such as metals, pesticides, and PCBs) has been shown to cause LM deficits after sub-chronic exposure (Roelens et al, 2005;Lidsky and Schneider, 2003;Ishimine et al, 2003). However, from the behavioral effects, it is difficult to deduce information about underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as PHAHs cause a disturbance in circulating levels of thyroid hormones, it could produce a negative effect on the HPT system leading to thyroid dysfunction (48). In vitro and in vivo studies showed that exposure to PHAHs at high concentrations causes a decreased T4 concentration and a hypothyroid state (49). Exposure to congener-specific PHAHs causes a decrease in circulating thyroid hormone levels that results in an increased secretion of pituitary thyroid stimulating hormone (TSH).…”
Section: Pbdes and Thyroid Functionmentioning
confidence: 99%
“…Increased gene expression in the fetal rat brain after maternal exposure to PCBs included neuroendocrine-specific protein A, neurogranin, myelin basic protein, and the transcription factors oct-1 and hairy enhancer of split (132)(133)(134), RC3/neurogranin and myelin basic protein in pups of PCB-treated dams (134). In a study of brain protein extracts from PCB-treated chicken embryos 17 of 109 differentially expressed proteins differed with PCB treatment (135). Malic enzyme (ME) gene expression is regulated mainly by THs and was increased by exposure to HCB, probably through still unidentified nuclear proteins that bind to the TRE of the ME promoter (136).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%